PEMANFAATAN WAKTU LUANG REMAJA di CAR FREE DAY KOTA PEKANBARU - Roeswin, Annerita Mutiara; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Utilization of leisure time for urban youth is urgently needed because theres a lot of activities carried out during normal day to force a teenager to get a day where they can take advantage of free time with activities favored. Teenagers of today can do something positive with a high sense of curiosity and desires can change their mind to be creative. Car-free day is a container teens to use their spare time with groups / friends. Car free day to do in this study is located at Jl. Diponegoro city of Pekanbaru. The purpose of this study was to determine the profile of adolescents who like what to spend their weekends in the car free day and wanted to know what activities are teens doing in the car free day. The method used in this research is qualitative method. In the authors use the data collection method accidental sampling. Observation comes with a photo camera. The interview was used in-depth interviews and on interview that has been prepared in advance. Supplies used at the time of the interview is a written record and voice recorder. Analysis of the data used in this research is the analysis of qualitative data. The results showed that the car-free day is a lifestyle for young people in the city of Pekanbaru. By participating in the activities of car free day teens can gather together a group / community and do something fun for theirself and get the satisfaction that can eliminate stress and burden of mind while at school or in college. When assembled with peers and alike hobby can frolic or sharing is concerned with the hobby and find a new friends, for urban youth it is powerful for refreshing.Keywords: Car free day, adolescents, lifestyle, the use of leisure time.